Management Intensity Modifies Plant Diversity Effects on N Yield and Mineral N in Soil. Issue 2 (3rd February 2015) - Oelmann, Yvonne; Vogel, Anja; Wegener, Florian; Weigelt, Alexandra; Scherer-Lorenzen, Michael
Abstract : The effect of species loss on productivity were of comparable magnitude to changes in agricultural management. However, not only productivity but also the N cycle is relevant for food production comprising beneficial as well as threatening effects of agricultural management. Our objectives were to test whether grassland management (mowing two or four times a year; 0, 100, or 200 kg N/ha) (i) modifies N yield or soil Nmin concentrations and changes (ii) the effect of plant functional groups (legumes, grasses, non‐leguminous small and tall herbs) on N yield or soil Nmin concentrations or (iii) the relationships between plant diversity and N yield or soil Nmin concentrations. We observed highest productivity under moderate management intensity which can be attributed to the growth‐stimulating fertilizer effect associated with enough time for regrowth. With increasing management intensity, the positive effect of the presence of legumes on N yield and soil Nmin concentrations disappeared. Plant species richness was positively related to N yield with the most pronounced effect in the highly fertilized and frequently mown treatment. In the control (mown twice a year, non‐fertilized), competition for nutrients very likely underlie plant species richness effects. Under higher management intensity, a combination of competition for light and adaption to mowing frequency seemed to be responsible for plant species richness effects. The concurrence of highest N yield in high‐diversity mixtures under most intensive management indicates that some plant species must have more than compensated for the N uptake of non‐adapted species that did not survive frequent mowing, highlighting the value of plant diversity as an insurance against anthropogenic disturbances including management measures.